PENGARUH BUDAYA ORGANISASI DAN PELATIHAN TERHADAP KINERJA PEGAWAI PADA PT. MARAHE INTI ALAM PERKASA LANGKAT - Ade Sitepu; Supriono (CV. Armas Suan Sejahtera, 2024)
Organizational culture needs to be transformed periodically according to the human resources (employees) in the company, so that the company's goals have an optimal impact on employee performance through training programs provided by the company which will also help to improve employee performance where optimal employee performance will be able to help companies in achieving goals are becoming faster. This study aims to determine and analyze the influence of organizational culture and training on employee performance at PT. Marahe Inti Alam Perkasa Langkat. The type of research used is associative. The sampling technique used was a total sampling technique with a total of fifty-five participants. The results of this study were obtained Organizational culture has a positive and significant effect on employee performance, with a tcount of 6,792> a t-table value of 2,006. Training has a positive and significant effect on employee performance, with a t-count of 11.064> a t-table value of 2.006 and organizational culture and training have a positive and significant effect on employee performance, with an F-value of 78.875> a t-table value of 3.170 or a significance value of 0.000 <alpha (0.05). Expected For companies, it can create an organizational culture and training that is more appropriate or in accordance with the working conditions of employees so that they are increasingly able to create and optimal employee performance.